Different Application Methods for Endoseal MTA Sealer: A Comparative Study - Moazami, Fariborz; Naseri, Mohammadhasan; Malekzade, Parastoo (Iranian Endodontic Journal, 2020)
Introduction: The aim of present ex vivo study was to investigate the ﬁlling quality and voids, using Endoseal mineral trioxide aggregate (Endoseal MTA) with a single-cone technique with and without ultrasonic application and to compare these methods with lateral compaction technique. Methods and Materials: Thirty-six extracted human anterior single-root teeth were prepared and assigned to 3 groups: Group 1: EMS group was Endoseal MTA+ single-cone; Group 2: EMSU group was Endoseal MTA+ single-cone with ultrasonic activation; and Group 3: LC group was Endoseal MTA+ lateral condensation technique. Teeth were sectioned transversely in coronal, middle and apical of the teeth and the existence of voidsand their areas in the slices were measured and scored under a dental microscope. One-way analysis of variance and Post Hoc test were used for statistical analysis and also to detect any significance (α=0.05). Results: EMS group showed significantly more void area than lateral compaction group (P<0.05), but the difference between the EMSU group and the other two groups were not significant (P>0.05). Also, EMS group had significantly higher void score than the other two groups (P<0.017). Conclusion: Endoseal MTA as a premixed calcium silicate sealer has a better performance when used with gutta-percha cone-mediated ultrasonic activation, so we suggest gentle ultrasonic activation for applying Endoseal MTA in the clinical use. Keywords: Mineral Trioxide Aggregate; Root Canal Obturation; Root Canal Sealer; Ultrasonic